2011
DOI: 10.1158/1078-0432.ccr-11-1142
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Agonist PSK Activates Human NK Cells and Enhances the Antitumor Effect of HER2-Targeted Monoclonal Antibody Therapy

Abstract: Purpose The therapeutic effect of trastuzumab monoclonal antibody (mAb) therapy has been shown to be partially dependent on functional NK cells. Novel agents that enhance NK cell function could potentially improve the anti-tumor effect of trastuzumab. We recently identified polysaccharide krestin (PSK), a natural product extracted from medicinal mushroom Trametes Versicolor, as a potent TLR2 agonist. The current study was undertaken to evaluate the effect of PSK on human NK cells and the potential of using PSK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 46 publications
6
54
0
Order By: Relevance
“…In this regard, TLR2 agonist treatment was proposed as adjuvant in cancer immunotherapy, 61 because it caused strong activation of NK cells in the context of ADCC induced by the therapeutic antibody Trastuzumab. 50 Our results are in line with recent evidence that exosome release in tumor cells was augmented in response to different drugs, including etoposide, 32 cisplatin and 5-fluorouracil. 43 In summary, our findings add new information on the immunomodulatory action of MM-derived exosomes during the course of chemotherapeutic interventions.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, TLR2 agonist treatment was proposed as adjuvant in cancer immunotherapy, 61 because it caused strong activation of NK cells in the context of ADCC induced by the therapeutic antibody Trastuzumab. 50 Our results are in line with recent evidence that exosome release in tumor cells was augmented in response to different drugs, including etoposide, 32 cisplatin and 5-fluorouracil. 43 In summary, our findings add new information on the immunomodulatory action of MM-derived exosomes during the course of chemotherapeutic interventions.…”
supporting
confidence: 91%
“…In line with these results, it was previously shown that IFNg production in response to PSK2, one of the known TLR2 agonists, was mainly associated to the NK CD56 high subset. 50 Thus, it is likely that the higher responsiveness of the CD56 high cell subset to exosome treatment mainly relies on its intrinsic ability to produce cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs or purified NK cells were prepared as previously described, and the purity of NK cells was approximately 99% (26). NK cell-mediated cytotoxicity was assessed by Calcein AM release from labeled target cells (26).…”
Section: Measurement Of Nk Cell Activity and Adcc Of Tumor Cellsmentioning
confidence: 99%
“…TLR2 agonist polysaccharide krestin (PSK) was also reported to activate human NK cells directly and indirectly with the help of IL-12. Notably, it can enhance the antitumor effect of HER2-targeted monoclonal antibody therapy [71]. In addition, a bacterial fimbrial protein FimH, a novel TLR4 ligand, was recently reported to directly activate human and murine natural killer cells via TLR4-MyD88 pathways [72].…”
Section: Tlr Signaling On Nk Cell Activationmentioning
confidence: 99%